Organocatalytic asymmetric selenofunctionalization of tryptamine for the synthesis of hexahydropyrrolo[2,3-b]indole derivatives - Wei, Qiang; Wang, Ya-Yi; Du, Yu-Liu; Gong, Liu-Zhu (Beilstein Journal of Organic Chemistry, 2013)
A chiral phosphoric acid-catalyzed selenofunctionalization of tryptamine derivatives provides access to 3a-(phenylselenyl)-1,2,3,3a,8,8a-hexahydropyrrolo[2,3-b]indole derivatives in high yields and with synthetically useful levels of enantioselectivity (up to 89% ee).
Keywords: catalysis; chiral phosphoric acid; hexahydropyrrolo[2,3-b]indole; indole alkaloids; natural products; selenofunctionalization

Selenium in Natural Product Synthesis - Nicolaou, K. C.; Petasis, N. A. (CIS, 1984)

Selenium Reagents and Intermediates in Organic Synthesis - Paulmier, C. (Pergamon Press, 1986)

Organoselenium Chemistry - Liotta, D. (Wiley & Sons, 1987)

The Chemistry of Organic Selenium and Tellurium Compounds - Back, T. G. (Preparative uses of organoselenium and organotellurium compounds, 1987)

Organoselenium Chemistry A Practical Approach - Back, T. G. (Oxford University Press, 1999)

Organoselenium Chemistry - Tiecco, M. (Electrophilic Selenium, Selenocyclizations, 2000)

(untitled) - Petragnani, N.; Stefani, H. A.; Valduga, C. J. (Tetrahedron, 2001)

(untitled) - Ranganathan, S.; Muraleedharan, K. M.; Vaish, N. K.; Jayaraman, N. (Tetrahedron, 2004)

(untitled) - Petragnani, N.; Ferraz, H. M. C. (Synthesis, 1978)

(untitled) - Reich, H. J. (Acc. Chem. Res., 1979)

(untitled) - Clive, D. L. J.; Chittattu, G. J.; Farina, V.; Kiel, W. A.; Menchen, S. M.; Russell, C. G.; Singh, A.; Wong, C. K.; Curtis, N. J. (J. Am. Chem. Soc., 1980)

(untitled) - Kraus, G. A.; Taschner, M. J. (J. Org. Chem., 1980)

(untitled) - Bachi, M. D.; Hoornaert, C. (Tetrahedron Lett., 1981)

(untitled) - Jones, D. N.; Mundy, D.; Whitehouse, R. D. (J. Chem. Soc. D, 1970)

(untitled) - Reich, H. J.; Wollowitz, S.; Trend, J. E.; Chow, F.; Wendelborn, D. F. (J. Org. Chem., 1978)

(untitled) - Rodriguez-Escrich, C.; Olivella, A.; Urpí, F.; Vilarrasa, J. (Org. Lett., 2007)

(untitled) - Deziel, R.; Goulet, S.; Grenier, L.; Bordeleau, J.; Bernier, J. (J. Org. Chem., 1993)

(untitled) - Deziel, R.; Malenfant, E. (J. Org. Chem., 1995)

(untitled) - Déziel, R.; Malenfant, E.; Thibault, C.; Fréchette, S.; Gravel, M. (Tetrahedron Lett., 1997)

(untitled) - Fragale, G.; Wirth, T.; Neuberger, M. (Chem. Commun., 1998)

(untitled) - Wirth, T. (Tetrahedron, 1999)

(untitled) - Wirth, T. (Angew. Chem., Int. Ed., 2000)

(untitled) - Tiecco, M.; Testaferri, L.; Marini, F.; Bagnoli, L.; Santi, C.; Temperini, A.; Sternativo, S.; Tomassini, C. (Phosphorus, Sulfur Silicon Relat. Elem., 2005)

(untitled) - Browne, D. M.; Wirth, T. (Curr. Org. Chem., 2006)

(untitled) - Denmark, S. E.; Kalyani, D.; Collins, W. R. (J. Am. Chem. Soc., 2010)

(untitled) - Hino, T.; Nakagawa, M. (Alkaloids, 1998)

Alkaloids: Chemical and Biological Perspectives - Anthoni, U.; Christophersen, C.; Nielsen, P. H. (Naturally occurring cyclotryptophans and cyclotryptamines, 1999)

(untitled) - Depew, K. M.; Marsden, S. P.; Zatorska, D.; Zatorski, A.; Bornmann, W. G.; Danishefsky, S. J. (J. Am. Chem. Soc., 1999)

(untitled) - Akiyama, T. (Chem. Rev., 2007)

(untitled) - Terada, M. (Chem. Commun., 2008)

(untitled) - Terada, M. (Synthesis, 2010)

(untitled) - Yu, J.; Shi, F.; Gong, L.-Z. (Acc. Chem. Res., 2011)

(untitled) - Huang, D.; Wang, H.; Xue, F.; Guan, H.; Li, L.; Peng, X.; Shi, Y. (Org. Lett., 2011)

(untitled) - Zhao, X.; Yu, Z.-K.; Xu, T.-Y.; Wu, P.; Yu, H.-F. (Org. Lett., 2007)

(untitled) - Hewitt, P. R.; Cleator, E.; Ley, S. V. (Org. Biomol. Chem., 2004)